Writer's bump - a case report - Padmasini Srinivasan; J Pranu Chakravarthy (Wolters Kluwer Medknow Publications, 2016)
A callus is a localized thickened part of skin occurring in regions of pressure like hands and feet. The following case report describes a case of callosity of right middle finger near the distal interphalangeal joint on the lateral aspect persisting from six years of age due to writing. This condition is otherwise called as a writer's bump. Callosities are acquired, superficial, circumscribed yellow white flat thickened patches of hyper keratotic material. They occur in areas of skin exposed to rubbing and pressure. In this case it is due to pencil holding. Paring of the lesion may be done by a fully trained chiropodist. Laser treatment is also given nowadays. Callosities are commonly found in hands and feet in areas exposed to frictional forces .They may have a genetic basis too .In this case it is inherited as autosomal dominant trait from the father.